Late Mesozoic - Early Cenozoic structural evolution of Sørvestsnaget Basin - Harsum, Wibi Aulia (2009)
Conclusion: This study focused on the structure and Late Cretaceous Early Cenozoic tectonic evolution of central part of the Sørvestsnaget Basin. Its location in the southwestern Barents Sea which is close to the Senja Fracture Zone makes this basin affected by the plate tectonic evolution. The evolution of the Sørvestsnaget Basin is divided into 5 stages during Late Cretaceous Cenozoic times: 1. Late Cretaceous down-faulting of the Sørvestsnaget Basin 2. Late Paleocene Early Eocene extensional / transtensional faulting associated with break up in the Norwegian Greenland Sea 3. Middle Late Eocene uplift of the marginal high in response to shear along and heat transfer across the continent-ocean boundary as the spreading ridge migrated along the Senja Fracture Zone. Narrowing / deepening of Sub-basin A and inversion of its NE flank also occurred in Late Eocene time and may be related tp uplift of the marginal high. 4. In Oligocene Early (?) Miocene, there was no major faulting but mild compression giving rise to minor folds. These could be similar to compressional structures observed widespread on continental margins surrounding the NE Atlantic. 5. Late Pliocene Pleistocene glaciations uplift / erosion of the Barents Shelf and subsidence / deposition of glacial fans along the western Barents Sea margin.